2001
DOI: 10.1007/s004150170181
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe dysfunction in essential tremor

Abstract: 27 patients with essential tremor (ET) were studied to determine the cognitive feature of this condition. 15 familial cases and 12 cases with a family history Parkinson's disease (PD) were identified. Performances on frontal lobe tasks of ET patients were compared with those of 15 patients with PD and 15 healthy control subjects. The ET patients showed significant impairments both in attentional and conceptual thinking tasks, similar to those observed in the PD group. Despite the nosographic independence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
161
2
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 18 publications
9
161
2
7
Order By: Relevance
“…Cognitive impairments related to impairments in the frontal-cerebellar circuit appear to be the most prominent feature of ET. 4 Despite the high prevalence of ET and the impact of cognitive impairments on quality of life, the spectrum and neural basis of these impairments are not fully characterized. Although a number of DTI studies have been conducted to better understand ET pathology, none have focused on the cognitive correlates of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairments related to impairments in the frontal-cerebellar circuit appear to be the most prominent feature of ET. 4 Despite the high prevalence of ET and the impact of cognitive impairments on quality of life, the spectrum and neural basis of these impairments are not fully characterized. Although a number of DTI studies have been conducted to better understand ET pathology, none have focused on the cognitive correlates of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown cognitive impairment, especially executive-visuospatial dysfunction and attention deficits, in patients with ET. 3,4 Voxel-based morphometry studies in ET have found volume reductions in the cerebellum and cerebrum (frontal lobe, insula, and cingulum). 5,6 While voxel-based morphometry analysis is useful for demonstrating regional GM changes, DTI provides information about the microstructural organization of WM.…”
mentioning
confidence: 99%
“…Patients also may have signs of more widespread cerebellar involvement (e.g., intention tremor, ataxia; Deuschl et al 2000;Singer et al 1994;Stolze et al 2000), abnormalities referable to the basal ganglia (e.g., rest tremor, subclinical signs of bradykinesia; Cohen et al 2003;Rajput et al 1993), and cognitive deficits (Gasparini et al 2001;Lombardi et al 2001). ET is considered to be distinct from age-related enhanced physiologic tremor, which has different clinical and electrophysiologic features (Louis et al 1997;Louis and Pullman 2001).…”
mentioning
confidence: 99%
“…Studies on this subject showed cognitive impairment with affected visuospatial abilities, verbal memory, executive functions, verbal fluency, naming and working memory in ET (12,33,34,35,36). Moreover, in a limited number of studies conducted with young patients, this condition has been proved to be present even at early stages (6,13).…”
Section: Discussionmentioning
confidence: 86%
“…In several studies, findings suggesting cerebral-thalamocortical tract dysfunction were found in patients with ET. Mild cognitive impairment characterized by impairment of visuospatial functions, verbal memory, and executive functions has been shown in young patients (8,9,10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%